1998
DOI: 10.1046/j.1525-1500.1998.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Stimulated Promotion of Tumors in the Gastrointestinal Tract

Abstract: Alcohol is a major risk factor for cancers of the upper gastrointestinal tract but the association with cancers of the large bowel is not as clearly established. In recent studies, we have provided experimental support for the associations in the esophagus and oral cavity. Our studies also indicate that the tumor promotion ability of ethanol is related to its ability to generate oxygen free radicals as measured by an increase in indices of lipid peroxidation. This increase in lipid peroxidation was evident in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…Additionally, taking the oxidative parameter analyses into account, it can be suggested that the damage in oral mucosa is cumulative and progressive. Our findings may only support the hypothesis that alcohol acts as a promoter, and not as an initiator, of oral cancer (Mufti, 1998). Nevertheless, the increase in cell proliferation may be the first step in oral carcinogenesis, since fast turnover tissues are more susceptible to DNA duplication errors (Melnick et al, 1993;Tomatis, 1993).…”
Section: Ventral Tongue Mucosacontrasting
confidence: 64%
“…Additionally, taking the oxidative parameter analyses into account, it can be suggested that the damage in oral mucosa is cumulative and progressive. Our findings may only support the hypothesis that alcohol acts as a promoter, and not as an initiator, of oral cancer (Mufti, 1998). Nevertheless, the increase in cell proliferation may be the first step in oral carcinogenesis, since fast turnover tissues are more susceptible to DNA duplication errors (Melnick et al, 1993;Tomatis, 1993).…”
Section: Ventral Tongue Mucosacontrasting
confidence: 64%
“…Alcohol is a tumor promoter; there is a positive correlation between alcohol intake and the risk of several human cancers, including mouth/oropharyngeal cancer, oesophageal cancer, liver cancer and breast cancer. [3][4][5][6][7][8][9][10][11] Epidemiologic studies indicate that alcohol consumption is associated with advanced and invasive breast tumors, [12][13][14] suggesting that alcohol may enhance tumor development and metastasis. These epidemiologic results are supported by experimental studies using animal models and cell culture systems, which show that ethanol promotes mammary tumorigenesis and stimulates proliferation as well as invasion of breast cancer cells.…”
Section: Abstract: Alcohol; Erbb; Metastasis; Proteinases; Signal Trmentioning
confidence: 99%
“…Ethanol consumption is causally linked to several human neoplasms, including primitive liver cancer [2]. Alcohol metabolism in liver cells leads to the formation of reactive oxygen species (ROS), which are responsible for hepatocyte damage, cellular apoptosis, and inflammation associated to excess alcohol consumption [3,4].…”
mentioning
confidence: 99%